Legal Analysis of Money Laundering Crimes from the Perspective of Transnational Organized Crime - Saputri, Fitri Arianti (PT. Anagata Sembagi Education, 2026)
The development of globalization has led to an increase in money laundering as part of transnational organized crime, which has serious impacts on economic stability and national legal systems. This study aims to analyze the legal provisions of money laundering within the national and international legal frameworks, and to examine the ambiguity of the norm regarding